2017
DOI: 10.1038/npp.2017.154
|View full text |Cite
|
Sign up to set email alerts
|

The Insular Cortex Dynamically Maps Changes in Cardiorespiratory Interoception

Abstract: Palpitations and dyspnea are fundamental to the human experience of panic anxiety, but it remains unclear how the brain dynamically represents changes in these interoceptive sensations. We used isoproterenol, a rapidly acting peripheral beta-adrenergic agonist similar to adrenaline, to induce sensations of palpitation and dyspnea in healthy individuals (n=23) during arterial spin labeling functional magnetic resonance imaging (fMRI). We hypothesized that the right mid-insular cortex, a central recipient of vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 49 publications
9
85
0
Order By: Relevance
“…Taken together, increased DLPFC and MOFC response to high-conflict trials in the emotional conflict Stroop at 1 week post-psilocybin task may reflect greater top-down control of emotionally conflicting information and IFG has been implicated in supporting a domain-general interference resolution process 69 . Activity in the anterior insula is understood to contribute to interoceptive mapping 70 , and both IFG and insula may be involved in the appraisal of social emotional stimuli 71 . The fusiform gyrus contains a number of functionally-defined sub-regions dedicated to stimulus-specific object recognition [72][73][74] , with specialized regions that respond to facial stimuli 75,76 .…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, increased DLPFC and MOFC response to high-conflict trials in the emotional conflict Stroop at 1 week post-psilocybin task may reflect greater top-down control of emotionally conflicting information and IFG has been implicated in supporting a domain-general interference resolution process 69 . Activity in the anterior insula is understood to contribute to interoceptive mapping 70 , and both IFG and insula may be involved in the appraisal of social emotional stimuli 71 . The fusiform gyrus contains a number of functionally-defined sub-regions dedicated to stimulus-specific object recognition [72][73][74] , with specialized regions that respond to facial stimuli 75,76 .…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that a discrete population of neurons in the posterior IC responded to both electric footshocks and tone during threat learning and the 24-h memory test (Berret et al, 2019). Also, imaging studies have shown that changes in the cardiorespiratory state are represented in the insula (Hassanpour et al, 2017), fear processing is modulated by cardiac activity (Garfinkel et al, 2014), and human fear-related disorders such as anxiety are associated with altered interoceptive processing in the insular cortex (Paulus and Stein, 2010;Simmons et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The prelimbic and ventral orbital regions of PFC, where we observed the greatest OxA-elicited neuronal activation, have been implicated in attentional shifting and reversal learning, respectively (Dalley et al 2004). We also observed robust activation in the agranular insular cortex, part of an area described as putative 'interoceptive cortex' because of its role in sensing the organism's physiological status (Craig and Craig 2002;Avery et al 2017;Hassanpour et al 2017). Given the role of orexin neurons in responding to peripheral cues indicative of physiological status, intranasal OxA may facilitate interoceptive processing within the insular region.…”
Section: Effects Of Intranasal Oxa On C-fos Expressionmentioning
confidence: 52%
“…; Hassanpour et al . ). Given the role of orexin neurons in responding to peripheral cues indicative of physiological status, intranasal OxA may facilitate interoceptive processing within the insular region.…”
Section: Discussionmentioning
confidence: 97%